Circulating trefoil factors in relation to lung cancer, age and lung function: a cross-sectional study in patients referred for suspected lung cancer. (1st October 2021) - Samson, Mie H.; Abildgaard, Anders M.; Espelund, Ulrick; Rasmussen, Torben R.; Folkersen, Birgitte; Frystyk, Jan; Nexo, Ebba
Abstract: The trefoil factor family proteins: TFF1, TFF2 and TFF3 are secreted by epithelial cells in the respiratory tract. Here, we explore circulating concentrations of the trefoil factors in relation to lung cancer, age and lung function. We included 751 patients suspected of lung cancer. Lung cancer diagnosis was based on data reported to a national database. Serum TFF1, TFF2 and TFF3 concentrations were measured by ELISA, and spirometry was performed within ±3 days of blood sampling. Forced expiratory volume in the first second (FEV1) in relation to forced vital capacity (FVC), FEV1/FVC (a parameter used to quantify reduced lung function) was recorded. Lung cancer was diagnosed in 163 (22%) patients. Circulating concentrations of TFF3 ( p  = .021), but not TFF1 and TFF2, were significantly elevated in cancer patients. All three trefoil factors showed an increase in concentration with increasing age ( p  < .001) and declining lung function ( p  < .004). In the present cohort, concentrations of all three peptides were elevated compared with previous results published for healthy individuals. In conclusion, we report higher concentrations of TFF3 in patients with lung cancer, while increasing age and reduced lung function are associated with increasing concentrations of all trefoil factors in this specific patient population. The results emphasize that age and lung function should be taken into consideration when evaluating concentrations of trefoil factors in patients. However, the increases in trefoil factor concentrations were relatively small, and consequently, it is unlikely that circulating trefoil factor concentrations may have a role in the diagnosis of lung cancer and lung function impairment.